Abundance of Culturable Bacteria Isolated from Maize Rhizosphere Soil Using Four Different Culture Media - ERNIN HIDAYATI; ARIS TRI WAHYUDI; ANTONIUS SUWANTO; RAHAYU WIDYASTUTI (Microbiology Indonesia, 2014)
Composition and abundance of culturable bacteria of four soil samples (Ktr50II, D50II, G50II, and A50II) were analyzed. The soil samples were collected from maize rhizosphere that planted in dryland Lombok Island. Each soil sample give different growth performance of maize in greenhouse experiment. This study was to investigate the relation of maize growth performance with culturable bacterial community of their rhizosphere and the effect of culture media on number of bacterial isolates recovery. The rhizosphere bacteria were cultured and isolated on commercial media (SEA) and non commercial modification media (NAln, NAln-SE and NAln- RE). Thirty four strains rhizosphere bacteria were obtained from four maize rhizophere soil samples. D50II is the soil sample that caused the better growth performance to the maize, contrary to Ktr50II. D50II has significantly highest number of culturable bacterial types, while significantly lowest on Ktr50II. In D50II, at least 17 bacterial isolates contributed to better growth performance in maize and have relative abundance of dominant isolate not more than 35.34%. In comparing the rhizosphere bacteria recovered using different culture media, bacteria cultivated on SEA have different growth characteristic compared with bacteria cultivated on NAln, NAln SE and NAln-RE. Six bacterial isolates showed antagonistic ability when grew on SEA but not in all of three media. Compared with commercial media, non commercial modification media can increase total isolates recovery about 70.6%.